Ramie Fibers from Agroforestry System as Sustainable Materials for Functional Textiles: A Review - Manggar Arum Aristri; Wahyu Hidayat; Apri Heri Iswanto; Muhammad Adly Rahandi Lubis (Department of Forestry, Faculty of Agriculture, University of Lampung, 2024)
Agroforestry system is a form of integrated land use involving forestry and agriculture, which is expected to help overcome the problems of increasing demand for agricultural land, decreasing environmental quality and poverty rates, and resulting in increasingly complex global issues. This system includes a combination of forestry crops with agricultural crops or other plants that can grow together on the same land. The application of agroforestry can improve agricultural welfare, overcome the environmental crisis and poverty, and maintain the sustainability of natural resource conservation. Ramie (Boehmeria nivea) fiber is an interesting plant to cultivate using an agroforestry system. It is easy to cultivate, positively impacts the environment, and has many application benefits because it is known as a strong and long-lasting fiber. On the other hand, the textile industry in Indonesia still predominantly uses cotton fiber which has low productivity, so the value of cotton imports increases yearly. Given the increasing demand for environmentally friendly and sustainable textiles, researchers and industry stakeholders are looking for other materials that provide functionality and environmental advantages. Ramie fiber is a type of natural fiber with advantages compared to other natural fibers, such as tensile strength, mechanics, and cellulose content, which has similar characteristics to cotton so that ramie can be applied as a functional textile material to replace cotton. This review paper aims to provide an in-depth overview of all ramie fiber properties, methods, and applications for functional textiles. This article highlights the environmental benefits of ramie fiber and its potential to encourage a more sustainable textile industry, citing various sources. Keywords: agroforestry, forestry crops, functional textile, ramie fiber, ramie’s properties